How to measure the impact of social innovation initiatives? - Cunha, Jorge; Benneworth, Paul (International Review on Public and Nonprofit Marketing, 2020)
Academic literature about the idea of social innovation grew sharply over the last decade, with researchers trying to define its concept and presenting several examples of successful social innovations. However, to support the development of social innovation initiatives is important to have a conceptual framework that allows evaluating its true impact. The purpose of this paper is to identify the boundary conditions for an effective set of social innovation indicators, which will help to have a more informed decision-making process. The main conclusion is that the impact of social innovations can be conceived as a set of results that manifests itself through different time periods, at different spatial scales, and must take into account the value experienced by all stakeholders involved. Thus, since a positive social innovation outcome depends on diverse factors and conditions, being most often context-dependent, it means that rather than imposing a specific set of indicators, based on a ‘one-size-fits-all’ approach a measuring process procedure should be adopted to assess the impact of social innovations.
Keywords: Mesure d'impact; Version libre-accès Open Repository